Vaginoplasty - Howard, Theresa (Operating Room Nurses Association of Canada Journal, 1987)
The congenital absence of a vagina was first described by Realdus Columbus in 1572 (Word, 1951). According to Jackson (1965), absence of a vagina is due to a failure of Mullerian duct develop- ment. The Mullerian ducts are embryonic tubes from which the oviducts, uterus and vagina develop in the female; in the male, they atrophy. Embryonic failure is usually complete when fallopian tubes are poorly developed, the uterus is rudimentary or absent, and there is no vagina. With a partial anomaly, the Mullerian tubercle fails to grow down and unite with the "up" growing urogenital sinus (Jackson, 1965).